A 126-cap of PG(5,4) and its corresponding [126,6,88]-code - Glynn, David G.; Tatau, Te Tari (Utilitas Mathematica, 2022)
A 126-cap is constructed in the finite projective space PG(5,4) of dimension five over GF(4), using the properties of conics in PG(2,4). It is shown to produce an interesting [126,6,88]-code.